2020
DOI: 10.1111/hsc.13010
|View full text |Cite
|
Sign up to set email alerts
|

The home care work environment’s relationships with work engagement and burnout: A cross‐sectional multi‐centre study in Switzerland

Abstract: This study aimed to investigate the levels of burnout and work engagement among home care workers in Switzerland and to test their association with job demands and job resources. We conducted a multi-centre, cross-sectional survey in the Germanspeaking part of Switzerland with a convenience sample of seven home care agencies. Data were collected between September 2017 and January 2018. We assessed burnout with the Maslach Burnout Inventory (MBI) and work engagement with the Utrecht Work Engagement Scale (UWES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 79 publications
(111 reference statements)
2
25
0
Order By: Relevance
“…This result is also consistent with previous studies indicating that technology use is associated with diverse types of work demands (Knani et al, 2018;Stich et al, 2015). Care work is a human-oriented occupation and emphasizes intensive interpersonal interactions with residents and the provision of person-centred care, which are highly physically and emotionally demanding and prone to burnout (Mockli et al, 2020). Within this context, the deployment of health technology (video gaming in particular) for residents in long-term care settings can, to some extent, mitigate the demanding aspects of work through reducing residents' dependency on caring, which might further buffer intention to withdraw from work.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is also consistent with previous studies indicating that technology use is associated with diverse types of work demands (Knani et al, 2018;Stich et al, 2015). Care work is a human-oriented occupation and emphasizes intensive interpersonal interactions with residents and the provision of person-centred care, which are highly physically and emotionally demanding and prone to burnout (Mockli et al, 2020). Within this context, the deployment of health technology (video gaming in particular) for residents in long-term care settings can, to some extent, mitigate the demanding aspects of work through reducing residents' dependency on caring, which might further buffer intention to withdraw from work.…”
Section: Discussionsupporting
confidence: 92%
“…Working in residential homes for older adults is labour-intensive and emotionally demanding. It is distinguished from working in other healthcare settings by the multifaceted health problems of residents, frequent interaction with residents and their families, comprehensive person-centred care, extended length of care required and high mortality rate of residents (Cooper et al, 2016;Mockli et al, 2020). In Hong Kong, each nurse or healthcare worker in a residential home needs to care for an average number of 60 residents (Social Welfare Department of Hong Kong SAR, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The mean working hours per week in three studies was 24.5 h per week 6,28,39 . Among the five studies which reported the proportion of study participants who had full‐time or part‐time jobs, less than half of the participants had full‐time jobs in three studies 11,41,47 …”
Section: Resultsmentioning
confidence: 99%
“…The education level of the study participants was reported in eleven studies. More than half of the participants completed high school or less in five studies, 16,35,39,43,45 and more than 70% of the participants attained college or higher education in another five studies 11,42,44,46,47 . The remaining study reported that 64% of study participants held home care certificates 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation